Simultaneous Determination of Four Water-Soluble Vitamins in Chinese Jujube (Ziziphus jujuba Mill.) by High-Performance Liquid Chromatography - Gao, Yan-Ru; Zhao, Zhi-Hui; Liu, Meng-Jun (Asian Journal of Chemistry, 2011)
A simple, fast and accurate liquid chromatography method for simultaneous separation and determination of vitamin B1 (thiamine), B3 (nicotinic acid), B6 (pyridoxine) and B2 (riboflavin) in Chinese jujube (Ziziphus jujuba Mill.), was developed and validated. The chromatographic separation was achieved on a Venusil XBP-C18 column at 25 ºC, using a gradient of water with 0.1 % phosphoric acid (pH 2.3) and acetonitrile at a flow rate of 0.8 mL/min. An ultra-violet detector (UV) was used to monitor the eluent at 270 nm with a total analysis time of 0.5 h. The method provided low limits of detection (LOD) and limit of quantification (LOQ), good linearity, accuracy and precision and had been successfully applied to the determination of water-soluble vitamins in five Chinese jujube cultivars. These studies could be vital interest for evaluating nutritional quality of Chinese jujube during production and at the end of shelf life.